1957
DOI: 10.2134/agronj1957.00021962004900010011x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Legumes in Corn1

Abstract: Synopsis Alfalfa was established successfully in corn by planting the alfalfa the same day as corn. High corn yields were obtained when a 20‐inch area over the corn row was kept weed free and the alfalfa between the rows was clipped. Sixty‐inch rows produced 92% and 80‐inch rows produced 80% as much corn grain as that produced in 40‐inch rows. Lespedeza and alfalfa were the easiest legumes to establish under summer seeding conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1959
1959
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…However, in other studies, available soil water could be the most limiting factor for the main crop growth in the north central United States (Eberlein et al, 1992) and in the U.S. Coastal Plain when the precipitation was below the long-term average (Ewing et al, 1991). Kurtz et al (1952) and Pendleton et al (1957) observed grain yield loss of corn which was grown with an interseeded legume due to soil water deficit conditions. Besides introducing cover crops and living mulches into conventional corn and soybean system, replacing the row crops with perennial forage, pasture, or native prairie is another option for water and water quality management.…”
Section: Introductionmentioning
confidence: 86%
“…However, in other studies, available soil water could be the most limiting factor for the main crop growth in the north central United States (Eberlein et al, 1992) and in the U.S. Coastal Plain when the precipitation was below the long-term average (Ewing et al, 1991). Kurtz et al (1952) and Pendleton et al (1957) observed grain yield loss of corn which was grown with an interseeded legume due to soil water deficit conditions. Besides introducing cover crops and living mulches into conventional corn and soybean system, replacing the row crops with perennial forage, pasture, or native prairie is another option for water and water quality management.…”
Section: Introductionmentioning
confidence: 86%
“…Pendleton et al, 1957;Scott and Patterson, 1962), has shown that the delay in sowing the pasture determines the degree of advantage conferred upon the crop. In our study, delayed sowing accentuated the effect of the intrinsically higher seedling growth rate of rice relative to stylo in promoting rice dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research with living mulches has focused on documenting and alleviating this problem (Liebman and Staver 2001;Teasdale, 1998). Many studies in the North Central U.S. on legume interseeding in established corn stands report grain yield losses that are attributed to moisture stress (Kurtz et al 1952;Pendleton et al 1957), N deficiency (Scott et al 1987;Triplett 1962), and reduced corn populations associated with wider row spacing (Schaller and Larson 1955;Stringfield and Thatcher 1951). Marks (1993) also suggested that reduced growth of the main crop may be due to competition for water or some other limited resource, or the mulch may be having an allelopathic effect.…”
Section: Competition Between Living Mulch and Main Cropmentioning
confidence: 99%